2015
DOI: 10.15356/0373-2444-2015-5-69-82
|View full text |Cite
|
Sign up to set email alerts
|

Paleosoils as an Indicator of Climate Change in the Late and Middle Pleistocene of the Center of the East European Plain

Abstract: Поступила в редакцию 14.11.2014 г. В разрезах лёссово-почвенной серии центральной части Восточно-Европейской равнины палеопочвы микулинского межледниковья формировались по текстурно-дифференцированному типу с преобладанием процессов лёссиважа и возможного оподзоливания в схожих климатических условиях с современным климатом. Палеопочвы каменского межледниковья содержали признаки процессов оглинивания и лёссиважа и формировались в более гумидных условиях, чем палеопочвы микулинского межледниковья. Палеопочвы инж… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…It may be concluded that the Kamenka interstadial paleosols are practically identical to those of Krutitsa in their characteristic. In the Gololobovo, Mikhnevo, Ozherelye sections in the studied region the paleosols are comparable with imperfectly developed modern Gleyic Phaeozems (Panin 2007(Panin , 2015Velichko and Morozova 2015). Paleosols of the Korostelyovo, Sebryakovo-Mikhailovka, Strelitsa-2017 and Gun'ki sections are attributed to imperfectly developed Kastanozems and Haplic Kastanozems, or to imperfectly developed Haplic Chernozems.…”
Section: The Middle Pleistocene Kamenka Paleosol Complexmentioning
confidence: 55%
See 3 more Smart Citations
“…It may be concluded that the Kamenka interstadial paleosols are practically identical to those of Krutitsa in their characteristic. In the Gololobovo, Mikhnevo, Ozherelye sections in the studied region the paleosols are comparable with imperfectly developed modern Gleyic Phaeozems (Panin 2007(Panin , 2015Velichko and Morozova 2015). Paleosols of the Korostelyovo, Sebryakovo-Mikhailovka, Strelitsa-2017 and Gun'ki sections are attributed to imperfectly developed Kastanozems and Haplic Kastanozems, or to imperfectly developed Haplic Chernozems.…”
Section: The Middle Pleistocene Kamenka Paleosol Complexmentioning
confidence: 55%
“…1) were analyzed by the authors of this paper and partly published in their earlier works. Among the sections, are Gololobovo (Panin 2007;Panin 2015;Little et al 2002;Chizhikova et al 2007), Ozherelye and Mikhnevo (Panin 2007), Suvorotino (Panin 2007), Bogolyubovo (Velichko et al 1996), Likhvin (Little et al 2002), Bryansk and Arapovichi (Velichko and Morozova 1963;Morozova 1981), Korostelyovo (Velichko 2002), Sebryakovo-Mikhailovka (Velichko et al, 2006), Gun'ki (Velichko et al 1997) and Strelitsa-2017. In those sections the Late Pleistocene (Mezin paleosol complex, PC) and Middle Pleistocene (Kamenka PC and Inzhavino PC) paleosols were exposed together with the surface soils.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations